Aplikasi Cendawan Mikoriza Arbuskula (CMA) Pada Pembibitan Lada Satu Ruas Berdaun Tunggal - Yan Sukmawan; Made Same; Bambang Utoyo (LPPM UNINUS, 2018)
Average production of pepper obtained from the of farmers in Air Naningan regency is between 350-450 kg/ha/year, which still very low, so that they must be helped to overcome the problems. The purpose of this activity was to conduct the pepper seedlings have mycorrhiza technologies. The methods that used include a survey to identify the feasibility and desire targeted farmers, extension with a lecture and sharing, training, and demonstration plots. The output from extension program was increasing knowledge, understanding, and skills farmer members in applying the pepper seedlings have mycorrhiza technologies so that cultivation can become a sustainable pepper production and became a mainstay of alternative sources of income of targeted farmers. In addition, these activities can increase Politeknik Negeri Lampung role in efforts to disseminate applied technology in an effort to improve social welfare in Lampung. Keywords : MFA, pepper seedling, single internode seedling